Pengaruh Strategi Bisnis Logistik Terhadap Kinerja Perusahaan Distributor Karpet Bandung (DKB) dengan Transformasi Digital Sebagai Variabel Moderasi - Waskito, Saptono Kusdanu; Rahayu, Muji (Pascasarjana STIE Amkop Makassar, 2025)
Bandung Carpet Distributor (DKB), a company engaged in selling and distributing plastic carpets in Bandung, is facing a performance issue, reflected in a sales revenue decline of IDR 200,000,000 in 2024 compared to the revenue in 2023. Despite implementing Business Logistics Strategies and Digital Transformation initiatives in 2024, DKB continues to encounter performance challenges.The author titles this article: Pengaruh Strategi Bisnis Logistik Terhadap Kinerja Perusahaan Distributor Karpet Bandung (DKB) dengan Transformasi Digital Sebagai Variabel Moderasi.The research findings describe that the average scores for Business Logistics Strategy, Digital Transformation, and DKB Performance are classified as satisfactory and meet the criteria for analysis. The questionnaire has been proven valid and reliable as a tool for collecting data from respondents. The study reveals: A positive and significant influence of Business Logistics Strategy on DKB Performance, A positive and significant influence of Digital Transformation on DKB Performance, A positive and significant influence of Business Logistics Strategy on DKB Performance, with Digital Transformation acting as a moderating variable. To address its performance challenges, DKB should implement improvements, such as purchasing plastic carpets at lower prices, reducing the selling price of plastic carpets, and establishing a same-day task force to expedite carpet distribution to locations in Bandung, Cimahi, Ngamprah, Soreang, and Sumedang. Kata Kunci : Bandung Carpet Distributor, Business Logistics Strategy, Digital Transformation, DKB Performance